Colloquial Polish as the material of press utterances (on the basis of selected examples) - Wojtak, Maria (Papers in Linguistics, 2021)
The starting point of the author’s analysis is colloquial Polish as the linguistic material of press utterances. The material base consists of two journalistic articles and a feuilleton from “Gazeta Wyborcza” of 2019. The author focuses on the scope of use of colloquial forms in generically marked concrete texts and on how these forms are adjusted to tasks the authors assigned to the utterances. The researcher does not endeavor to search for communication regularities of general nature. She moves from the macro plane to the micro plane to show the editorial virtuosity of the authors of concrete utterances. Colloquial (mainly lexical) forms are embedded in textual constructs unknown to colloquialism, and undergo original stylistic processes. In the first text they are elements of a court report, in the second – of a few microstories and in the third text they are a realization of the principle of feuilleton conceptismo resulting from contamination of the pattern of an illustrative story and a report on clinical symptoms of a disease.